HEPATITIS A VIRUS INFECTION IN CHILDREN (Iraqi Journal of Medical Sciences, 2016)
Background: most hepatitis A viral infections in children are asymptomatic or have mild non specific manifestations but some are complicated.Objective: to evaluate all cases of hepatitis A viral infection in children who were admitted over one year period and enlighten out the abnormal presentations and predict complications.Patients and methods: during the period from 1st of June 2005- 1st of June 2006, fifty cases of hepatitis A viral infection (who had hepatitis A virus IgM +ve) were studied and analyzed regarding the clinical presentations, coarse of the illness, complications and outcome.Results: fifty patients enrolled in the study, with male to female ratio of 1.8:1 and 32 (64%) of them presented in the age of 1-5 years.Fulminant hepatic failure was found in 7 (14%) cases, 5 (10%) had prolonged cholestasis , 5 (10%) had exacerbation of pre- existing chronic liver disease, 2 (4%) had recurrent or relapsing hepatitis A viral infection, and 5 (10%) cases had extra hepatic manifestations , 3 (6%) were G6PD deficient patients who had sever hemolysis.Conclusions: hepatitis A viral infection can present in different ways.The level of consciousness, presence of ascites and severely abnormal biochemical and hematological values were of great help in predicting complicated cases of hepatitis A viral infection.Key words: hepatitis A, abnormal presentations, children.
Keywords: hepatitis A; abnormal presentations; children